2023
DOI: 10.1001/jamaoto.2023.1944
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Functional and Survival Outcomes Between Patients Receiving Primary Surgery vs Chemoradiation Therapy for Treatment of T1-T2 Oropharyngeal Squamous Cell Carcinoma

Abstract: ImportanceDue to lack of data from high-powered randomized clinical trials, the differences in functional and survival outcomes for patients with oropharyngeal squamous cell carcinoma (OPSCC) undergoing primary transoral robotic surgery (TORS) vs primary radiation therapy and/or chemoradiation therapy (RT/CRT) are unclear.ObjectivesTo compare 5-year functional (dysphagia, tracheostomy dependence, and gastrostomy tube dependence) and survivorship outcomes in patients with T1-T2 OPSCC receiving primary TORS vs R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
1
0
1
Order By: Relevance
“…[18][19][20] Compared to radiotherapy alone, TORS also has advantages, Dev R Amin et al reported in 2023 that patients who received TORS surgery for T1-T2 oropharyngeal SCC had an decreased risk of shortterm and long-term gastrostomy tube dependence and better 5-year overall survival compared with patients who received radical radiotherapy. 21 Another randomised controlled trials reported by Anthony C Nichols in 2019 also showed that TORS combined with neck dissection had a lower incidence of neutropenia, hearing loss and tinnitus than radiotherapy alone. 22 In addition, It is worth emphasising that all 11 patients completed TORS and neck dissection at the same surgery.…”
Section: Gastric Tube Implantationmentioning
confidence: 99%
“…[18][19][20] Compared to radiotherapy alone, TORS also has advantages, Dev R Amin et al reported in 2023 that patients who received TORS surgery for T1-T2 oropharyngeal SCC had an decreased risk of shortterm and long-term gastrostomy tube dependence and better 5-year overall survival compared with patients who received radical radiotherapy. 21 Another randomised controlled trials reported by Anthony C Nichols in 2019 also showed that TORS combined with neck dissection had a lower incidence of neutropenia, hearing loss and tinnitus than radiotherapy alone. 22 In addition, It is worth emphasising that all 11 patients completed TORS and neck dissection at the same surgery.…”
Section: Gastric Tube Implantationmentioning
confidence: 99%
“…Sin embargo, la cirugía mediante un abordaje transoral se asocia a una morbilidad significativamente menor que la abierta (28,29) y puede considerarse un tratamiento electivo en función de la extensión y localización de la lesión. Aunque algún estudio retrospectivo ha mostrado una mayor supervivencia en tumores precoces con cirugía transoral frente a RTQT, los sesgos existentes no han permitido dilucidar qué herramienta terapéutica es la más conveniente (30)(31)(32).…”
Section: Generalidadesunclassified

Role of radiotherapy in early head and neck cancer

Gómez-Millán Barrachina,
Toledo Serrano,
Martin Romero
et al. 2024
Rev Cancer
“…This database has been increasingly used to investigate pressing epidemiologic questions for diverse, complex, and acute conditions including outcomes related to cancer, SARS-CoV-2 infection, liver disease, cardiovascular health, and psychiatry conditions. [11][12][13][14][15] Here, we employed a descriptive framework similar to our prior investigation of the prevalence of MS, 16 including direct standardization to estimate the number of NMOSD cases in the United States in 2022.…”
Section: Introductionmentioning
confidence: 99%